2005
DOI: 10.1007/s10517-006-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of cultured astrocytes attenuates degenerative changes in rats with kainic acid-induced brain damage

Abstract: Viability of astrocyte grafts introduced into CA1 pyramidal layer of the left dorsal hippocampus after injection of kainic acid into this brain region and the effects of these grafts on the hippocampus and amygdala were studied on Wistar rats. In rats with astrocyte grafts the degree of destruction in fields CA1-CA2 of the dorsal and ventral hippocampus, fields CA3-CA4 of the ventral hippocampus, and central and basolateral amygdala was lower compared to animals with kainic acid-induced hippocampal damage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(16 reference statements)
2
4
0
Order By: Relevance
“…Therefore, the territories of loss of astrocyte support correlated with the neuron-damaged area in both NMDA- and KA-injected cortexes (Figs. 1 and 3), indicating that reactive astrocytes protect neurons in the injured brain as previously reported in several brain injury models (Ermakova et al, 2005; Haj-Yasein et al, 2012; Myer et al, 2006; Rothstein et al, 1992; 1995; Shi et al, 2012; Zeng et al, 2012). …”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Therefore, the territories of loss of astrocyte support correlated with the neuron-damaged area in both NMDA- and KA-injected cortexes (Figs. 1 and 3), indicating that reactive astrocytes protect neurons in the injured brain as previously reported in several brain injury models (Ermakova et al, 2005; Haj-Yasein et al, 2012; Myer et al, 2006; Rothstein et al, 1992; 1995; Shi et al, 2012; Zeng et al, 2012). …”
Section: Discussionsupporting
confidence: 72%
“…A loss of EAAT2/GLT-1 and decreased glutamate transport have been identified in human ALS patients (Rothstein et al, 1992; 1995). In addition, astrocyte functional loss precedes neuronal death in spinal cord injury (Min et al, 2012), and transplantation of human astrocytes facilitates functional recovery after the injury (Ermakova et al, 2005; Myer et al, 2006). In the previous study, we showed that in ATP-injected brain, astrogliosis occurs and delayed neuronal death is absent (Jeong et al, 2013c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, neurons can not live without support of astrocytes. Accordingly, it has been reported that selective ablation of reactive astrocytes exacerbates traumatic neuronal damage and that transplantation of astrocytes diminishes brain damage [18, 19]. We also found spatial-temporal correlation between delayed neuronal death and functional loss and/or death of astrocyte in the spinal cord injury [2].…”
Section: Introductionsupporting
confidence: 68%
“…Astrocytes provide neurons with glucose and neurotrophic factors, and protect neurons from oxidative stress and excitotoxicity through glutathione (GSH) production, glutamate and potassium uptake, and modulation of water content [11-17]. Accordingly, it has been reported that ablation of astrocytes augments traumatic neuronal damage, and that transplantation of astrocytes diminishes brain damage [18,19]. …”
Section: Introductionmentioning
confidence: 99%